Karakteristik Kompos Dari Limbah Kulit Buah Pada CV. Mahajaya Sangkara, Bali Food Industry Dengan Perlakuan Konsentrasi Effective Microorganism 4 (EM4) - Puspaningrum, Ade; Triani, I Gusti Ayu Lani; Anggreni, Anak Agung Made Dewi (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
Fruit skin waste still contains many organic compounds that can be processed into environmentally friendly, useful, and value added products, one of which is compost. The addition of EM4 bioactivator to composting can affect composting time faster than natural composting. This study aims to determine the effect of EM4 concentration treatment on the characteristics of compost from fruit skin and determine thebest compost characteristics with the addition of EM4 according to SNI 19-7030-2004. The experimental design used wasia Group Randomized Design with EM4 concentration as a treatment consisting of five levels namel 0%, 25%, 50%, 75%, 100%. The treatment was grouped into 3 groups based on the time of its implementation so that 15 experimental units were obtained. The obtained are analyzed-for-variance and-if the treatment affects the observed variables, it is continued with the Honest Real Different Test (BNJ). The results showed that the addition of EM4 bioactivator had a very real effect on the temperature, pH, color, and yield of compost but had no effect on the organic matter content of compost. The best treatment that produces characteristics according to SNI 19-7030-2004 is the addition of EM4 bioactivator by 75% which produces compost with compost temperature characteristics of 32.22±0.07oC, compost pH 7.23±0.06, compost color L* 3.67±0.58, a* 0.33±0.58, b* 2.67±0.58, organic matter content 28.68±7.14%, and yield 51.11±0.96%.